Pregunta
upstudy study bank question image url

\( 3^{2 x-y}=\frac{1}{81} \) and \( x^{2}+3 x y-3 x-9 y=0 \)

Ask by Garrett Stewart. in South Africa
Feb 20,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The solutions are: - \( x = 3 \), \( y = 10 \) - \( x = -\frac{12}{7} \), \( y = \frac{4}{7} \)

Solución

We are given the system:   (1) 3^(2x – y) = 1/81   (2) x² + 3xy – 3x – 9y = 0 Step 1. Express Equation (1) in Exponential Form Write 1/81 as a power of 3. Since 81 = 3⁴, we have:   1/81 = 3^(–4) Thus, Equation (1) becomes:   3^(2x – y) = 3^(–4) Because the bases are the same and are positive (and not equal to 1), the exponents must be equal:   2x – y = –4 Rearrange to solve for y:   y = 2x + 4 Step 2. Substitute y into Equation (2) Replace y in Equation (2) with the expression from Step 1:   x² + 3x(2x + 4) – 3x – 9(2x + 4) = 0 Expanding the terms:   x² + 6x² + 12x – 3x – 18x – 36 = 0 Combine like terms:   (1x² + 6x²) + (12x – 3x – 18x) – 36 = 0   7x² – 9x – 36 = 0 Step 3. Solve the Quadratic Equation We now solve: 7x² – 9x – 36 = 0 Using the quadratic formula, x = [–b ± √(b² – 4ac)] / (2a), where a = 7, b = –9, and c = –36:   Discriminant, D = (–9)² – 4(7)(–36) = 81 + 1008 = 1089 Since 1089 is a perfect square (√1089 = 33), we have:   x = [9 ± 33] / (2 × 7) Find the two solutions:   x = (9 + 33) / 14 = 42 / 14 = 3   x = (9 – 33) / 14 = (–24) / 14 = –12/7 Step 4. Find the Corresponding y-values Recall that y = 2x + 4. For x = 3:   y = 2(3) + 4 = 6 + 4 = 10 For x = –12/7:   y = 2(–12/7) + 4 = –24/7 + 28/7 = 4/7 Step 5. Present the Solutions The system has the following two solutions:   Solution 1: x = 3, y = 10   Solution 2: x = –12/7, y = 4/7 Both pairs satisfy the original equations.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To solve the equation \( 3^{2x-y}=\frac{1}{81} \), we first rewrite \( \frac{1}{81} \) as \( 3^{-4} \). This gives us: \[ 2x - y = -4 \] Next, we can isolate \( y \): \[ y = 2x + 4 \] Now we can substitute this expression for \( y \) into the second equation: \[ x^2 + 3xy - 3x - 9y = 0 \] Substituting \( y \): \[ x^2 + 3x(2x + 4) - 3x - 9(2x + 4) = 0 \] Expanding this we get: \[ x^2 + 6x^2 + 12x - 3x - 18x - 36 = 0 \] Combining like terms: \[ 7x^2 - 9x - 36 = 0 \] Now, we can solve this quadratic equation using the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \): Here, \( a = 7 \), \( b = -9 \), and \( c = -36 \): Calculating \( b^2 - 4ac \): \[ (-9)^2 - 4(7)(-36) = 81 + 1008 = 1089 \] Now, finding the roots: \[ x = \frac{9 \pm \sqrt{1089}}{14} \] The square root of 1089 is 33, leading us to: \[ x = \frac{9 \pm 33}{14} \] Calculating the positive and negative cases: 1. \( x = \frac{42}{14} = 3 \) 2. \( x = \frac{-24}{14} = -\frac{12}{7} \) Now substituting \( x = 3 \) back into \( y = 2x + 4 \): 1. For \( x = 3 \): \[ y = 2(3) + 4 = 10 \] 2. For \( x = -\frac{12}{7} \): \[ y = 2\left(-\frac{12}{7}\right) + 4 = \frac{8}{7} \] (after simplifying) The solutions to the original equations are: - \( (x, y) = (3, 10) \) - \( \left(-\frac{12}{7}, \frac{8}{7}\right) \)

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad